Exploring the Impact of AI Chatbots on Students’ Speaking Skills in EFL Learners: A Systematic Review - Rachmadani, Khulud Oktavia; Musyafa`ah, Isna Ridhoatul; Asti Hijriatul Januanto; Ima Fitriyah (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
AI chatbot is one of the latest technologies in solving EFL students' problems with speaking anxiety and limited speaking practice. In this study, we conduct a Systematic Literature Review for the investigation of the effect of using AI chatbots on EFL students' speaking skills and learners' perceptions toward the use of AI chatbots in speaking skill improvement. We followed the SALSA framework, which includes Search, Appraisal, Synthesis, and Analysis to direct our work. We searched Lens.org and Google Scholar databases for articles. The articles published from 2020 to 2025. We also conducted a thematic analysis within 24 identified articles. Overall, evidence shows students benefit greatly by practicing with AI chatbots. Students who do so make gains in vocabulary, grammar, fluency, pronunciation, and foreign language speaking anxiety (FLSA) and thus feel more motivated to communicate in the target language, as students find bots to be a less critical audience. However, this meta-analysis did find a lack of evidence about the disadvantages of chatbot use. There are also the general limitations of AI, such as the tendency to output the same response for different inputs, and AI's inability to replace the teacher's contextual feedback. Thus, the study finds that AI chatbots are an effective and useful tool for improving EFL speaking ability when used in moderation and as a complement to teacher-led instruction in the classroom.